Spirituality transformation from metaphysical to metaverse - Nurasih, Wiji; Latifah, Ainiyatul; Mohamed, Adil Hassan Ibrahim (IAS Journal of Localities, 2023)
Human spirituality experiences dynamics, develops, and transforms along with the shifting of human culture and civilization from time to time. Auguste Comte has categorized the intellectual development stages into three, namely theological stage, metaphysical stage and positive stage. The three stages of intellect have a big contribution in shaping the living of spirituality in every age. However, today and in the future, humans will face a new civilization when they enter the digital world. Experts in digital technology field continue to develop new worlds that transcend reality and call it the metaverse. This research is intended to explain human spirituality in the shift from the metaphysical stage to the metaverse and to find out what has changed during the shift of these waves. The writer feels that this study is important since spirituality is an integral part of human life and requires full awareness in living it. The data to be used in this study were obtained by reviewing the literature (library research) and analyzed using the continuity and change theory. By using this theory, it is expected that this research will be able to find out what is sustainable and what changes in human spirituality in the course of the three waves above.